2023
DOI: 10.1101/2023.11.13.566813
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Azole resistance: Insights from Y132 substitutions inCandidasterol 14α-demethylase

R. Shyama Prasad Rao,
Larina Pinto,
Renuka Suravajhala
et al.

Abstract: BackgroundAzole-resistantCandidainfections are on the rise. Resistant substitutions at Y132 in sterol 14α-demethylase, the key target of azole drugs, are frequent. However, it is unclear why only some Y132 substitutions are favoured or how they exert differential effects on different azoles.Materials and MethodsReported instances of Y132 substitutions were collected from the literature. Extensive molecular dynamics simulations of sterol 14α-demethylase bound to fluconazole or VT1161 (VT1) were performed, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 51 publications
(61 reference statements)
0
0
0
Order By: Relevance
“…Further, it provides insightful patterns -for example, the number and abundance of substitutions in each Candida species. It may be noted that when there were multiple substitutions, they came from different clinical/experimental isolates and/or from different studies, and therefore provided an independent validation of such resistant substitutions/sites (Rao et al, 2024).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Further, it provides insightful patterns -for example, the number and abundance of substitutions in each Candida species. It may be noted that when there were multiple substitutions, they came from different clinical/experimental isolates and/or from different studies, and therefore provided an independent validation of such resistant substitutions/sites (Rao et al, 2024).…”
Section: Discussionmentioning
confidence: 99%
“…We searched the databases -PubMed/Medline, Scopus, Web of Science, and Google Scholarusing various combinations of the following keywords: "Candida", "azole resistance", "mutation/substitution", AND/OR "sterol 14α-demethylase", and sifted through the research papers to find the reports of experimentally confirmed azole-resistant substitutions in various clinical isolates (Rao et al, 2024). The review reports citing substitutions, if any, were traced to the original reports.…”
Section: Data Curation On Azole-resistant Substitutions In Sterol 14α...mentioning
confidence: 99%
See 3 more Smart Citations